2019
DOI: 10.1039/c8nj05827j
|View full text |Cite
|
Sign up to set email alerts
|

Binding and inhibitory effect of the food colorants Sunset Yellow and Ponceau 4R on amyloid fibrillation of lysozyme

Abstract: Amyloid fibrillogenesis of proteins is known to be the root cause of a large number of diseases like Parkinson's, Alzheimer's, and Huntington's disease, spongiform encephalopathy, amyloid polyneuropathy, type-II diabetes, etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Molecular docking is a useful method to evaluate the interactions of the ligand molecule with protein. [ 43,44 ] Thus, molecular docking studies were performed for chromate and dichromate with Lyz which provided evidence for their interactions on the Lyz. The binding free energy of dichromate and chromate to Lyz was identified to be −65.5 and −45.9 kJ mol −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking is a useful method to evaluate the interactions of the ligand molecule with protein. [ 43,44 ] Thus, molecular docking studies were performed for chromate and dichromate with Lyz which provided evidence for their interactions on the Lyz. The binding free energy of dichromate and chromate to Lyz was identified to be −65.5 and −45.9 kJ mol −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…26 These investigations demonstrated that sunset yellow binds to exposed hydrophobic surface such as solvent-accessible tryptophan residues. 26 Related to this, the binding of sunset yellow to pepsin has implications for its use as a food additive. A combination of fluorescence and molecular dynamic simulations reveals that sunset yellow causes an inhibition of pepsin, binding to a cluster of tyrosine and serine residues in the active site.…”
Section: ■ Introductionmentioning
confidence: 97%
“…The interaction of dye molecules with larger structures is of wide interest. Sunset yellow interactions with amyloid fibril aggregates of lysozyme have been studied using a range of biophysical techniques, including transmission electron microscopy and various fluorescence assays . These investigations demonstrated that sunset yellow binds to exposed hydrophobic surface such as solvent-accessible tryptophan residues .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carmoisine is an azo dye that binds with hen egg white lysozyme and shows an inhibitory effect on amyloid fibrillation in lysozyme [ 17 ]. Sunset Yellow (SY) and Ponceau 4R have also interacted with lysozyme at acidic pH and inhibiting temperature-induced amyloid fibrillation [ 18 ]. Keeping this in mind, we have evaluated the mechanism of interaction and amyloid-inducing property of SY on Beta-lactoglobulin (BLG) protein at acidic pH.…”
Section: Introductionmentioning
confidence: 99%